2014
DOI: 10.4172/2161-105x.1000203
|View full text |Cite
|
Sign up to set email alerts
|

Poor Oral Health as Risk Factor for Community-Acquired Pneumonia

Abstract: Objectives: Considerable evidence exists of the relationship between poor oral hygiene (therefore greater presence of plaque) and risk of pneumonia in special-care populations, including intensive care unit and nursing home settings. However, the effect of poor oral health on the development of community-acquired pneumonia (CAP) remains to be established. We assessed the relationship between CAP and oral health in general adult population. Study design:Over 1-year period, 1,336 incident cases of CAP and 1,326 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
3
0
2
Order By: Relevance
“…In consistent with this nding, a study from Korea (21) showed that frequent tooth brushing signi cantly decreased CAP. Another study from Spain (17) and Japan (10,20) also revealed that having poor dental hygiene increase a risk to develop CAP. This nding is also consistent with a study conducted in Tigray, Ethiopia (7,11).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In consistent with this nding, a study from Korea (21) showed that frequent tooth brushing signi cantly decreased CAP. Another study from Spain (17) and Japan (10,20) also revealed that having poor dental hygiene increase a risk to develop CAP. This nding is also consistent with a study conducted in Tigray, Ethiopia (7,11).…”
Section: Discussionmentioning
confidence: 94%
“…In this study, individuals who did not regularly brush their teeth were 2.8 times more likely to develop CAP than those who regularly brush their teeth on a daily basis. Many research in geriatric, nursing home, hospitalized, and intensive care unit patients (15)(16)(17)(18)(19) have reported an association between oral health and pneumonia. Again, a Japanese study (20) revealed infrequent denture cleaning was signi cantly associated with pneumonia incidence.…”
Section: Discussionmentioning
confidence: 99%
“…The oral hygiene and the incidence of aspiration pneumonia and nursing and healthcare-associated pneumonia (NHCAP) have been well established. 14 Many studies on geriatric, nursing home, hospitalized, and intensive care unit patients [17][18][19][20][21] have reported an association between oral health and pneumonia. Additionally, Japanese study 22 revealed that infrequent denture cleaning is significantly associated with the incidence of pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…išsivystymo rizika [23].Yra tiriamųjų darbų, įrodančių stiprią sąsają tarp burnos ertmės ligų ir VĮP išsivystymo rizikos padidėjimo. F. Rodriguez su bendraautoriais aprašė tiriamąjį darbą, kuriame pastebėjo, jog karštos arba šaltos medžiagos, sukeliančios dantų diesteziją -dantų ėduonies ar periodonto ligos rodiklis, dantų protezų dėvėjimas buvo nepriklausomi VĮP rizikos veiksniai [24]. Kiti mokslininkai pastebėjo, jog prasta burnos higiena gali kelti kvėpavimo takų infekcijų riziką [25,26].…”
Section: Visuomenėje įGytos Suaugusiųjų Pneumonijos Rizikos Veiksniaiunclassified
“…Įdomu tai, kad prasta burnos sveikata ir burnos bei žarnyno ligos padidino VĮP riziką tiek pagyvenusiems žmonėms, tiek visuomenei. Dantų apnašos ir dantų protezai skatina kolonizaciją ir gali būti kvėpavimo takų patogenų kaupimosi vieta [24], todėl mūsų praktinė išvada, svarbi VĮP rizikos grupės žmonėms, yra dantų apnašų ir bakterijų kaupimosi prevencija, ypač dėvintiems dantų protezus ir sergantiems dantų ėduonies ar periodonto ligomis. Išvados 1.…”
Section: Visuomenėje įGytos Suaugusiųjų Pneumonijos Rizikos Veiksniaiunclassified